Design of adjustable Tuned Mass Dampers using elastomeric O-rings. (27th October 2018) - Tang, N.; Rongong, J.A.; Sims, N.D.
Abstract: Tuned mass dampers (TMDs) are widely used in passive vibration control, and have been implemented on many engineering structures. In general, the design of TMDs is unique to each application; the choice of damping material and its in-situ performance are key issues that can affect design and prototyping costs. The present contribution demonstrates that TMDs can be built using ubiquitous and low-cost elastomeric O-rings. It is shown that the damping and stiffness characteristics of the O-ring can be predicted a priori, in order to achieve an initial design that is fit for purpose. Furthermore, it is shown that the nonlinear characteristics of the O-ring enable the device to be easily tuned in-situ, in order to optimise the final system. Finally, the simple configuration of the device makes it well suited to through-mounting or surface-mounting on thin-walled flexible structures such as beams and plates.